Territorial Strategic Planning as a support instrument for Regional and Local Development : a comparative analysis between Lisbon and Barcelona metropolitan areas - a first approach - Marques, Bruno Miguel Pereira (2013)
Trabalho de Projecto apresentado para cumprimento dos requisitos necessários à obtenção do grau de Mestre em Metropolização, Planeamento Estratégico e Sustentabilidade.